Housing in the EU: The EU as a commodifying force - Jonathan Sidenros (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2025)
This study explores the European Union's role in Europe's housing crisis. While much attention has been given to the EU's impact on other welfare state sectors, housing remains underexplored. Using Aalbers' theory of housing financialisation and Scharpf's theory of positive and negative EU integration, this study examines four modes of housing financialisation: mortgage debt, mortgage securitization, financialisation of rental housing, and financialisation of social housing companies. The findings suggest that the EU has contributed to housing commodification through channels such as mortgage market liberalisation, fiscal regulations, monetary policy, capital mobility, and competition law. A hierarchical struggle emerges between the single market and local housing administration, with EU law dominating this relationship through negative integration, since the elimination of market barriers, whether between or within member states, is at the essence of the single market project. This stands in contrast to the EU's commitments to housing as a human right. By highlighting housing as the primary surplus absorber of capitalism, and by integrating Aalbers theory of housing financialisation with Scharpf's theory of EU integration, this study underscores the essential role of housing in the broader EU integration process, i.e. housing commodification is shown to be both a driver and product of the EU's political economy. On a positive note, a theoretical argument can be made of the potential of EU housing to escape the determinism inherent to the negative integration perspective. Housing right obligations in EU treaties do exist, which offer the possibility for housing integration based on social commitments rather than market forces.
Keywords: P1; P16; R1; 330; Financialisation of housing; economic geography; EU integration; welfare state transformation; commodification; decommodification